Spiritual Interventions in Juvenile Delinquency - (:unkn) unknown (My University, 2018)
This study is a review on spiritual and religious oriented interventions for juvenile delinquents. The article iscomposed of five parts, namely: (i) juvenile delinquency, (ii) the relationship between crime and spirituality,(iii) spiritual interventions for juvenile delinquency, (iv) spiritual interventions in prison for delinquentchildren, and (v) spiritual interventions in schools for delinquent children and their family. In the first part,the definition and scope of juvenile delinquency and the factors for committing a crime are given. In thesecond part, theories of spiritual psychology concerning juvenile delinquency are expressed. Faith-basedintervention approaches, group psychological consultation approaches, and the spiritual interventions andcounseling proficiencies of positive psychology’s spiritual intervention and counseling proficiencies arediscussed in the third part. In last part, space has been given to in-school interventions and preventionapproaches for families.

Bu çalışma suça sürüklenen çocuklarda maneviyat ve manevi yönelimli müdahalelere ilişkin bir derlemedir. Makale beş bölümden oluşmaktadır. Bu bölümler çocuk ve ergen suçluluğu, suç ve maneviyat ilişkisi, suça sürüklenen çocuklarda manevi müdahaleler, okullarda suça sürüklenen çocuklara ve ailelere yönelik müdahale ve önleme yaklaşımları, ceza ve infaz kurumlarında suça sürüklenen çocuklar için manevi temelli müdahalelerdir. İlk bölümde çocuk suçluluğunun tanımı, kapsamı, suça sürükleyen etkenlere yer verilmiştir. İkinci bölümde, suçu açıklayan manevi psikolojinin teorilerine değinilmiştir. Üçüncü bölümde bu çocuklar için geliştirilen inanç temelli müdahale yaklaşımları, grupla psikolojik danışma yaklaşımları, pozitif psikolojinin manevi müdahalesi, danışmanlık yeterlilikleri anlatılmıştır. Son bölümde ise suça sürüklenmiş çocuğa sahip ailelere ve okulda çocuklar için geliştirilmiş manevi müdahalelere yer verilmiştir.
Suça Sürüklenen Çocuklarda Manevi Müdahaleler
Keywords: Psikoloji